Neonatal intestinal microbiota factors - Mularczyk, Agata; Stangret, Anna; Szczęśniak, Angelika; Topczewska, Katarzyna; Rogulska, Karolina (Journal of Education, Health and Sport, 2020)
Intestinal microbiota is a key element in maintaining health. Recently, the relationship between the microbiome and specific disease entities has been emphasized. A relationship between the composition of commensal flora and obesity, allergies, cancer and autism is suggested. Studies are available on factors that affect the formation of bacterial microflora in newborns. The pregnant microflora may affect the unborn baby. The study found the presence of bacteria in amniotic fluid, umbilical cord blood, placenta and fetal membranes. The microbiome of newborns born by caesarean section remove the one found on the mother's skin and function and in the operating room while the newborn born by nature pathways is close to the microflora of the mother's vagina. There was also a difference in the microbiome of newborns born in the hospital and at home. Breastfeeding also affects the intestinal microflora. Mother's milk and infant faeces show the same bacterial strains. Intestinal dysbiosis may be the basis for a number of disease entities. It is necessary to know the prenatal and postnatal properties influencing the gastrointestinal colonization of the newborn. This knowledge will help develop guidelines favorable for normal colonization with microorganism of the neonatal intestines.